The Effect of Standing Mats on Biomechanical Characteristics of Lower Limbs and Perceived Exertion for Healthy Individuals during Prolonged Standing - Yan Zhang; Yining Xu; Zixiang Gao; Hongjun Yan; Jianshe Li; Yichen Lu (Applied Bionics and Biomechanics)
Objective. To identify the effect of standing mats on biomechanical characteristics of lower limbs and perceived exertion for healthy adult individuals during a prolonged standing task. Methods. 32 healthy college students were recruited in the randomized and cross-over designed trial according to the effect size and statistical power. After collecting the anthropometric data, each participant was asked to finish 2 sessions of 4-hour prolonged standing tasks on standing mats (MS) and hard ground (GS) in a random order and with a 72-hour interval rest. The plantar pressure distribution, foot morphology, and scores of the BESS (balance error scoring system) would be recorded pre- and posteach task. The Borg Rating of Perceived Exertion (RPE) would be collected during the whole task. Paired-samples t test was adopted to analyse the before and after difference within group and independent-samples t test was adopted to analyse the difference between groups separately. Results. (1) A prolonged standing task on both MS and GS have a negative effect on RPE and balance performance. (2) The negative effect on RPE and balance performance induced by MS is significantly smaller than that induced by GS. (3) Compared to GS, prolonged standing on MS has a lower peak plantar pressure and an implicit decrease in navicular drop and AHI (arch index). Conclusion. Standing mat tends to alleviate the fatigue induced by prolonged standing in lower limbs, optimize the distribution of plantar pressure, and maintain the stability.